2020
DOI: 10.1177/2058739220934559
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect of Tβ4 on central nervous system tissues and its developmental prospects

Abstract: Tissue repair and regeneration in the central nervous system (CNS) remains a serious medical problem. CNS diseases such as traumatic and neurological brain injuries have a high mortality and disability rate, thereby bringing a considerable amount of economic burden to society and families. How to treat traumatic and neurological brain injuries has always been a serious issue faced by neurosurgeons. The global incidence of traumatic and neurological brain injuries has gradually increased and become a global cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 98 publications
2
16
0
Order By: Relevance
“…It is fascinating in the contexts of AD also, the antimicrobial and anti-inflammatory activities of thymosin β4 ( Carion et al, 2020 ) that was found to be more abundant in the saliva of AD patients than in HCs. Tβ4 is the most abundant Tβ in human tissues, including CNS, where it exerts multiple biological functions, such as downregulation of inflammatory chemokines and cytokines, promotion of cell migration, blood vessel formation, cell survival, stem cell maturation, inhibition of microbial growth, and antiapoptotic factor on gingival fibroblasts ( Hannappel, 2007 ), as well as neuroprotective and neuroregenerative effects ( Chopp and Zhang, 2015 ; Zhang et al, 2020 ). The increased level of Tβ4 in saliva from AD patients is interesting and probably reflects an increase in the brain, in view of the elevated levels of Tβ4 found in reactive microglia of AD patients, where it suppresses the pro-inflammatory signaling ( Zhang et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…It is fascinating in the contexts of AD also, the antimicrobial and anti-inflammatory activities of thymosin β4 ( Carion et al, 2020 ) that was found to be more abundant in the saliva of AD patients than in HCs. Tβ4 is the most abundant Tβ in human tissues, including CNS, where it exerts multiple biological functions, such as downregulation of inflammatory chemokines and cytokines, promotion of cell migration, blood vessel formation, cell survival, stem cell maturation, inhibition of microbial growth, and antiapoptotic factor on gingival fibroblasts ( Hannappel, 2007 ), as well as neuroprotective and neuroregenerative effects ( Chopp and Zhang, 2015 ; Zhang et al, 2020 ). The increased level of Tβ4 in saliva from AD patients is interesting and probably reflects an increase in the brain, in view of the elevated levels of Tβ4 found in reactive microglia of AD patients, where it suppresses the pro-inflammatory signaling ( Zhang et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“… 28 The cross‐linking of Tb4 or other beta thymosins is probably a general mechanism for binding to extracellular structures such as fibrin and collagen and its action as a chemotactic or regulator of the inflammatory response at both the systemic and cerebral levels. 28 , 29 The regulation of infiltration into the central nervous system (CNS) of CD4+T cells, which occurs through adhesion molecules and ligands present in the blood–brain barrier, plays a fundamental role in the transition between the neurodegenerative and neurosuppressive phenotypes of the microglia. 30 Thus, the predominance of one or other pathway will depend on the numerical and functional predominance of the T cells present, whether they are effector or regulatory.…”
Section: Discussionmentioning
confidence: 99%
“… 35 According to a recent report, based on Tβ4 potential anti‐inflammatory molecules and neuroprotective and myelin regeneration molecules and their mechanism of action, Tα1 and Tb4 could be used alone to treat multiple sclerosis (MS) or with other approved applications of drug combination therapy. 29 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to antimicrobial activity, it is well established that Tβ-4 is a multifunctional peptide that plays a vital role in wound healing, promoting the repair and regeneration of injured cells and tissues 133,143,144 . Given the alkaline pH associated with wounds 21,145 , it has been suggested that the enhanced antimicrobial activity of the peptide under these pH conditions may be an adaptation that allows Tβ-4 to fight microbial infection as a part of the wound healing process 146 .…”
Section: Amps From Mammalsmentioning
confidence: 99%